Ultrasound-Guided versus Conventional Caudal Block in Children: A Prospective Randomized Study - Karaca, Omer; Pinar, Huseyin Ulas; Gokmen, Zeynel; Dogan, Rafi (European Journal of Pediatric Surgery, 2019)
Background Injection to the accurate area without any complications is the main factor for the efficiencies of caudal block. The aim of this study was to compare success and the complications of conventional and ultrasound method for caudal block in children.Materials and Methods Two-hundred sixty-six American Society of Anesthesiologists (ASA) category 1 children aged between 6 months and 6 years undergoing hypospadias, circumcision, or both surgeries were randomly allocated two groups (Group C or Group H, n = 133). About 0.25% bupivacaine with 1/200000 adrenaline (total volume: 0.5 mL/kg) was injected after the needle was inserted into the sacral canal in Group C, or right after the needle pierced the sacrococcygeal ligament under longitudinal ultrasound view in Group H. Success rate of block, block performing time, number of needle puncture, success at first puncture, complication rate, age and weight of the patients encountering these complications were recorded.Results The success rate of block was similar between two groups (94.7% in Group C vs 96.2% in Group U, p > 0.05). Success at first puncture was higher in Group U than in Group C (90.2 vs 66.2%, respectively; p < 0.001). Number of needle puncture, blood aspiration, subcutaneous bulging, and bone contact was higher in Group C but none in Group U (p < 0.001) and these complications were occurred in children weighing < 16 kg and less younger than 6 years old.Conclusion We observed that the complications were not encountered, number of needle puncture was lesser, and the success rate of first puncture was higher under ultrasound with longitudinal view.
Keywords: caudal block; children; ultrasound; conventional method